Implications for the origin and evolution of Martian Recurring Slope Lineae at Hale crater from CaSSIS observations. (August 2020) - Munaretto, G.; Pajola, M.; Cremonese, G.; Re, C.; Lucchetti, A.; Simioni, E.; McEwen, A.S.; Pommerol, A.; Becerra, P.; Conway, S.J.; Thomas, N.; Massironi, M.
Abstract : Recurring Slope Lineae (RSL) are narrow, dark features that typically source from rocky outcrops, incrementally lengthen down Martian steep slopes in warm seasons, fade in cold seasons and recur annually. In this study we report the first observations of RSL at Hale crater, Mars, during late southern summer by the Color and Surface Science Imaging System (CaSSIS) on board ESA's ExoMars Trace Gas Orbiter (TGO). For the first time, we analyze images of RSL acquired during morning solar local times and compare them with High Resolution Imaging Science Experiment (HiRISE) observations taken in the afternoon. We find that RSL activity is correlated with the presence of steep slopes. Our thermal analysis establishes that local temperatures are high enough to allow either the melting of brines or deliquescence of salts during the observation period, but the slope and aspect distributions of RSL activity predicted by these processes are not consistent with our observations. We do not find any significant relative albedo difference between morning and afternoon RSL. Differences above 11% would have been detected by our methodology, if present. This instead suggests that RSL at Hale crater are not caused by seeping water that reaches the surface, but are best explained as dry flows of granular material. Highlights: We report the first CaSSIS observations of RSL at Hale crater, Mars. We compare morning CaSSIS images with afternoon HiRISE observations. We do not find any relative albedo variations between morning and afternoon RSL. RSL lengthening is constrained to steep slopes. Our results indicate that RSL are consistent with dry flows.